Geograafia-alaseid töid. IV, Pühendatud XX Rahvusvahelisele geograafia kongressile = Publications on geography : on the occasion of the XXth International Geographical Congress = Труды по географии : посвященный XX-му Международному географическому конгрессу - Tartu Ülikool (Tartu Riiklik Ülikool, 1964)
• E. Varep. The landscape-regions of Estonia • Resümee • Резюме • E. Hang. T. Liblik and E. Linkrus. On the relations between Estonian valley terraces and lake and sea levels in the Late-Glacial and Holocene periods • Resümee • Резюме • V. Lepasepp. On the application of the landscape principle to the study of land resources • Resümee • Резюме • S. Nõmmik. On the economic regionalization of the Estonian S. S. R. • Resümee • Резюме • T. Rea. On the ways of development and genetic classification of Estonian urban settlements • Resümee • Резюме • E. Varep. Count L. A. Mellin and his "Atlas of Livonia" • Resümee • Резюме • Raik. Data on Kamchatka geysers • Resümee • Резюме • E. Varep. The Geography Department of Tartu State University • Resümee • Резюме • Contents. Sisukord. Содержание http://tartu.ester.ee/record=b1247052~S1*est